Alat Pelacak Lokasi Berbasis GPS Via Komunikasi Seluler - Wijaya, Surya Purba; Christyono, Yuli; Sukiswo, Sukiswo (Departemen Teknik Elektro, Universitas Diponegoro, 2010)
Nowadays, the vehicle’s robbing or the usage of not allowed route is often happen. Therefore, vehicle tracking system is needed to reduce this risk. Vehicle tracking system is a system’s combination that installed in the vehicle so that can be tracked by the owner or the third part. Modern vehicle tracking system usually use GPS to determine vehicle’s location. This system also usually have communication component such as cellular or satellite to send vehicle’s position to user in another place. In this Final Project, the vehicle tracking tool based on GPS via cellular will be created. This tool is a part of vehicle tracking system. This tool will respond a command which is sent by tracker via SMS. The device contains of three parts. There are microcontroller as a control part, GPS which provide positioning information, and GSM modem which is used to send or receive message. All of these parts will cooperate to process all of the messages sent by tracker. Then server will get information about position in form of longitude, latitude, date and time. This device will be tested in case of receiving’s delay at tracker side, timer’s precision, location’s precision which is showed by GPS, vehicle tracking. Based on testing, there are varying receiving delay at traker side. Timer has ran well so that getting data appropriate to the interval which is asked. Position which is showed by GPS is not precision in fact. However, the tracking can be done and similar with the fact in the field.Keyword : GPS, vehicle tracking system, cellular communication